Language, ethnic conflicts and international law - De Varennes, Fernand (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2011)
Most of the world's contemporary conflicts can be described as ethnic conflicts. Though the contexts and players are always different, and the factors involved can be as numerous and diverse as the countries where these conflicts occur, there remains nevertheless an overall pattern which is discernible: most of these conflicts involve minorities, and most of these minorities have grievances against state authorities in the lead-up to the eruption of violence. After considering a number of conflicts in Asia and other parts of the world, this article considers whether it is possible to view these grievances as having a valid basis from the point of view of international law, and more ambitiously, what lessons may be extracted from such an understanding of the underlying causes of ethnic conflicts.
Keywords: mednarodno pravo; etnični konflikti; jezikovne pravice; Azija; Šrilanka; Tajska; človekove pravice; human rights; manjšine